Sistem Monitoring Tekanan Air pada PDAM Gianyar Berbasis Web - Ni Wayan Sumartini Saraswati; I Wayan Agustya Saputra (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2019)
Regional Water Company (PDAM) Gianyar Regency is one of the regionally owned companies in Gianyar Regency. Gianyar PDAM is responsible for the availability of clean water for consumers in the Gianyar region and its surroundings. In a water distribution system, the PDAM monitors water pressure in the pipeline so that water is guaranteed to flow to the customer. During this time the system of recording water pressure on the manometer installed in each particular zone is done manually using report paper. The difficulty caused is the slow monitoring of water pressure reported by the recording officer to the distribution officer, so that the water distribution process becomes stagnant which ultimately harms the customers and the PDAM itself. This study aims to create a system that can record water pressure which makes it easier for the distribution head to get information quickly. With the research phase which includes data collection techniques, system analysis, and system design to maximize research and implement systems and tests on each system, it can be concluded that the system that has been made can run well and as expected. The functional features generated in this study are the dashboard graph of the average water pressure per month, processing master employee data, processing village master data, processing master manometer data, processing schedule data, manometer monitoring by officers, manometer monitoring by admin and manometer monitoring report .